The ghosts of Galway - Bruen, Ken (Bruen, Ken. Jack Taylor novels., 2017)
"As well-versed in politics, pop culture, and crime fiction as he is ill-fated in life, Jack Taylor is recovering from a mistaken medical diagnosis and a failed suicide attempt. In need of money, and with former cop on his resume, Jack has been hired as a night-shift security guard. But his Ukrainian boss has Jack in mind for a bit of off-the-books work. He wants Jack to find what some claim to be the first true book of heresy, The Red Book, currently in the possession of a rogue priest who is hiding out in Galway after fleeing a position at the Vatican. Despite Jack's distaste for priests of any stripe, the money is too good to turn down. Em, the many-faced woman who has had a vise on Jack's heart and mind for the past two years, reappears and turns out to be entangled with the story of The Red Book, too, leading Jack down to ever more mysterious and lethal pathways. It seems all sides are angling for a piece of Jack Taylor, but as The Ghosts of Galway twists toward a violent end, he is increasingly plagued by ghosts--by the disposable and disposed of in a city filled with as much darkness as the deepest corners of Jack's own mind"--